2013
DOI: 10.1007/s10404-013-1171-3
|View full text |Cite
|
Sign up to set email alerts
|

Transient flow behavior of complex fluids in microfluidic channels

Abstract: The ongoing development of microfluidic devices involves the use of highly complex fluids, even of multiphase systems. Despite the great achievements in the development of numerous applications, there is still a lack in the complete understanding of the underlying physics of the observed macroscopic effects. One prominent example is the flow through benchmark contractions where microand even macroscopic explanations of some of the occurring flow patterns are still missing. Here, we study the development of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…that entanglement effects are weakened significantly at high strain rates, at which even concentrated solutions exhibit behaviours that resemble those of dilute solutions''. Then, as in the references, 38,39 the initial relaxation from a non-equilibrium somewhat disentangled and aligned configuration is simply the Rouse time.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…that entanglement effects are weakened significantly at high strain rates, at which even concentrated solutions exhibit behaviours that resemble those of dilute solutions''. Then, as in the references, 38,39 the initial relaxation from a non-equilibrium somewhat disentangled and aligned configuration is simply the Rouse time.…”
Section: Discussionmentioning
confidence: 86%
“…scaling of Z(0), l CY , etc.). Indications of the underlying cause for this apparent discrepancy can be seen in relaxation measurements of 2% (w/v) polyacrylamide solutions (5-6 MDa) after a single extensional flow that have been reported experimentally 38 and theoretically. 39 The combination of experiment and theoretical analysis lead to a picture where the extensional flow stretches and aligns the polymer molecules such that the relaxation process from this configuration ''is analogous to that considered in single-chain stretching experiments'', i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested by previous authors that this relaxation process could be used to obtain an experimental measure characteristic times of complex fluids (e.g. Klessinger et al 2013;Litvinov et al 2014). However, we believe the high shear rates that are imposed on the localized regions of stretched fluid as they flow downstream within the capillary may significantly affect such a measurement by perturbing the relaxation of extensional stress.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier numerical results of Alves et al (2003) show that the length required for relaxation of the normal stress increases with the Weissenberg number, thus suggesting that very long outlet channel lengths may be required in order to ensure fully developed flow of highly elastic fluids. For shear-thinning viscoelastic fluids in a capillary entrance geometry, Klessinger et al (2013) observed a relaxation process from an initially parabolic shape to a flattened steady-state flow profile in the narrow channel. In addition, the entrance length against Wi was quantitatively diagrammed, revealing a power-law dependency.…”
Section: Introductionmentioning
confidence: 94%
“…[14][15][16][17][18][19][20][21][22][23][24][25] A number of studies on aqueous polymer solutions have been conducted through contraction/contraction-expansion flows. 7,12,[14][15][16][17][26][27][28][29][30][31][32][33][34][35][36][37][38][39] When viscoelastic solution flows through a contraction throat, different characteristic flow regimes may appear in the upper stream region of the contraction throat with the increasing flow rate. Lip vortices, elastic corner vortices, diverging flows, and time-dependent unstable flows were observed in contraction channels.…”
Section: Introductionmentioning
confidence: 99%